Peran Kompetensi Karyawan Terhadap Loyalitas Karyawan Dimediasi Knowledge Sharing dan Job Performance - Uut Kumalasari; Ika Yoga (Social Science Studies, 2022)
The purpose of this study was to analyze the role of employee competence, knowledge sharing, work loyalty in improving employee performance (Study on employees at PT. Pos Indonesia, Sragen). The population in this study were all employees of PT. Pos Indonesia Sragen Regency both at the branch and at the center. The sample in this study were 71 respondents. Data were analyzed using IBM SPSS Statistics version 22 software.This research method is a quantitative research method. The data analysis method uses path analysis. The results showed that: (1) employee competence had no effect on employee performance. (2) knowledge sharing has an effect on employee performance (3) work loyalty has an effect on employee performance.The findings of this study indicate that knowledge sharing and work loyalty can improve employee performance. However, employee competence cannot improve employee performance. So the company should seek programs that can improve employee performance, especially by providing counseling, training, mentoring and supervision to improve their competence and will further improve the performance of employees.